High treatment effectiveness for secondary effluent in Fe–C microelectrolysis constructed wetlands with electron donor supplementation. (15th March 2022) - Ji, Bohua; Jiang, Ming; Yang, Ying; Deng, Shengjiong; Chen, Jinquan; Chang, Junjun
Abstract: The deep purification of secondary effluent from wastewater treatment plants (WWTPs) is essential for protecting the receiving water environment. Recently, iron-carbon materials have attracted more and more attention for treating secondary effluent. In this study, lab-scale iron-carbon microelectrolysis constructed wetlands (Fe–C CWs) filled with iron scraps (ISs) and granular biochar were established to purify secondary effluent with C/N ratios of 0.5–5. Walnut shells or pyrite were amended as organic or inorganic electron donors to enhance nutrient removal and reduce iron consumption. The IS substrate substantially promoted nutrient removal when the C/N ratio ≤2 (20.3–36.5% for nitrogen and 10.4–21.8% for phosphorus) by supplying Fe 2+ /H2 for autotrophic denitrification and iron compounds for phosphorus sequestration. Walnut shell supplementation further strengthened nutrient removal, achieving excellent effluent water quality. Fe substrate consumption was alleviated by electron donor supplementation. The IS substrate decreased CO2 emissions while increasing CH4 and N2 O fluxes of the biochar-based CWs, and pyrite addition mitigated the global warming potential (GWP) of the Fe–C CWs. When the C/N ratio changed from 5.0 to 0.5, the abundance of autotrophic denitrifiers and Fe cycle-related populations dominated by Dechloromonas, Ferritrophicum and Thiobacillus increased notably in ISs-amended CWs, and they were responsible for the efficient nitrogen removal. Fe–C CW supplemented with organic solid wastes presents high potential for advanced purification of low C/N nitrified effluent. Graphical abstract: Image 1 Highlights: Autotrophic denitrification dominated in CWs filled with iron scraps (ISs) and biochar at COD/TN ≤ 2. Walnut shell addition effectively enhanced nutrient removal in Fe–C CWs. Fe substrate loss was mitigated by electron donor addition. Pyrite addition reduced greenhouse gas emissions from Fe–C CWs. IS amendment largely increased the abundance of autotrophic denitrifiers in CWs.